The Use of Hydrolyzed Palm Kernel Cake After Addition by Buffalo Rumen Fluid Enzymes on Growth Performances and Relatively Organ Weight of Broilers - Agus Budiansyah; Ucop Haroen; Anie Insulistyowati; Syafwan Syafwan (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
This study aims to utilize a sufficient amount of palm kernel cake (PKC) and buffalo rumen fluid as a source of enzymes to improve the quality of PKC that can be used in broiler feed. The study was conducted in two stages. The first stage was to test the level of buffalo rumen fluid enzyme at various doses (0.0%, 0.75%, 1.5%, 2.25%, and 3.0% (v/w) in PKC incubation to measure dry matter (DM), organic matter (OM), crude fiber (CF), and dissolved glucose total (DGT) contents as hydrolyzed PKC. The second stage was to determine the usage level of hydrolyzed PKC in broiler feed. A total of 288 DOC MB202 strains were randomly allocated to one of five treatments with four replicated cages of 12 birds in a completely randomized design. Treatments were the various level of hydrolyzed PKC as following: 0%, 6%, 12%, 18%, 24%, and 30%. The variables were feed consumption, body weight gain (BWG), feed conversion ratio (FCR), final body weight (FBW), carcass, and digestive organs weight. The level of buffalo rumen fluid enzymes had a significant effect on DM, CF, and DGT content, while it was not significant on OM. The optimum level was 2.25% and it was used in the second stage. The use of hydrolyzed PKC up to 18% was not different (P>0.05) in BWG, FCR, and FBW compared to controls. The use of hydrolyzed PKC up to 24% decreased BWG, FCR, and FBW, but feed consumption did not differ (P>0.05) compared to control. Carcass and digestive organ weight were not affected (P>0.05) by the treatment. It can be concluded that the incubated buffalo rumen fluid enzymes at a level of 2.25% could improve the quality of PKC. The use of hydrolyzed PKC could be applied up to 18% without affecting the performance of broilers